An effective evapotranspiration estimation scheme based on statistical indicators for sustainable environments in humid and semi-arid area of Khyber Pakhtunkhwa, Pakistan. Issue 3 (30th December 2021) - Gul, Sajid; Ren, Jingli; Xiong, Neal; Fawad, Muhammad
Abstract: Reference evapotranspiration (ETo ) is critical for irrigation design and water management in rainfed and irrigated agriculture. The Penman-Monteith (FAO-56(PM)) equation was demonstrated to be the most reliable and adaptive to a wide range of humid to semi-arid climates. However, it requires several environmental parameters (e.g., wind speed, solar radiation), rarely available in developing countries. Therefore, numerous temperature-based formulas have been designed to address this issue for various environments. Their calibration and validation against the local climate frequently lead to increases in performance. We revised the Hargreaves exponent (EH ) and substituted a value of (0.16) for the original value (0.5). The modified Hargreaves formula enhances the ETo predictions with a mean absolute error ranging from (0.791) mm per day for Balakot to (2.36) mm per day in Risalpur, averaging (3.797) mm per day, as compared to the Hargreaves-Samani (16.827) mm per day. In general, all the selected models showed high accuracy. However, the modified Hargreaves equation appeared to give the most promising results. It ranked first in (50%) of the whole area based on the standard error of estimate for estimating ETo in Khyber Pakhtunkhwa. Additional research must be conducted to determine the study's relevance to other regions. HIGHLIGHTS: The main objective of this paper is to investigate the possibility of calibrating the Hargreaves equation and comparison for spatial domain Khyber Pakhtunkhwa, Pakistan. The performance evaluation of three radiation-based methods (Priestly-Taylor, Makkink and Turc) and two temperature based methods (Hargreaves-Samani and modified Hargreaves) are evaluated in this paper. Bayesian Kriging is used for interpolation. Graphical Abstract